Current Tendencies in Postgraduate Theses Written in the Field of Art Education in Turkey - (:unkn) unknown (ICLEL CONFERENCES, 2018)
The education activities that are performed for the purpose of expressing thoughts and impressions and raise the talent and creativity to an aesthetic level are expressed as art education. The purpose of this study is to examine the postgraduate theses conducted on art education in Turkey. The study was conducted as a qualitative study and the data were collected through the document analysis method. The research data were analyzed through content analysis. 74 postgraduate theses on art education that were searched by the term Art Education on YOK (Council of Higher Education) National Thesis Center database were accessed. 54 of the 74 postgraduate theses are master's theses and 20 of them are PhD dissertations. Among these theses, in total 48 theses were examined as 12 PhD dissertations and 36 master's theses. For the purpose of examining the theses accessed, the Thesis Examination Form was developed by the researchers towards the objective of the study. In this context, all of the open access -postgraduate theses that were conducted on the field of art education between the years of 2012-2017 were grouped from various aspects. The general assessments of the theses were made according to the institutes that they are affiliated with, years, universities, study groups, research models and data collection tools. In terms of the data analysis, frequency (f) was utilized and the findings were presented on graphs. According to the obtained data, most of the theses (11) were conducted on the years between 2014 and 2015. Between the years of 2012 and 2017, Gazi University is in the first place among the Turkish universities with the number of theses conducted in the field of art education. While qualitative methods (25) were preferred in the theses predominantly, quantitative methods followed the given situation. Almost all of the theses (%90) were conducted in an Institute of Education Sciences. Furthermore, the most frequently used data collection tool was a document/archive. Moreover, while the studies were conducted towards students they were designed as document oriented, and in the level of higher education, they were designed as prospective teacher/undergraduate student -oriented.
Keywords: Art Education; Postgraduate Theses; Art Education Studies